2022
DOI: 10.1177/00027642221118280
|View full text |Cite
|
Sign up to set email alerts
|

Old Rules for New Times: Sportswomen and Media Representation in the COVID-19 Pandemic

Abstract: During the first few months of the pandemic, professional sport around the globe stopped, as competitions and leagues were cancelled, postponed, or went into hiatus while sport administrators scrambled to work out ways to reboot their product in a COVID-19 world. Sport media outlets were faced with the task of reporting on sport and filling the void for fans in the absence of any live content. This article is concerned with the content, both in quantity and quality that fans of women’s sport could consume in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Ambivalent coverage is that which diminishes the sporting achievements of athletes by shifting focus away from their athletic success by pairing positive statements with statements focusing on faults or aspects unrelated to sport that undermine athleticism 80. It is a well-documented sport media pattern which marginalises and trivialises women athletes 80 81. An analysis of articles published by ESPN.com and ESPNW.com found that 59% of articles published about women athletes were ambivalently framed, while only 11% of articles published about men athletes were ambivalently framed 82.…”
Section: Resultsmentioning
confidence: 99%
“…Ambivalent coverage is that which diminishes the sporting achievements of athletes by shifting focus away from their athletic success by pairing positive statements with statements focusing on faults or aspects unrelated to sport that undermine athleticism 80. It is a well-documented sport media pattern which marginalises and trivialises women athletes 80 81. An analysis of articles published by ESPN.com and ESPNW.com found that 59% of articles published about women athletes were ambivalently framed, while only 11% of articles published about men athletes were ambivalently framed 82.…”
Section: Resultsmentioning
confidence: 99%